Kurva Kerapuhan Seismik Pada Struktur Rangka Baja Berbasis Pushover - Pramesta Praba Sumedi; Rita Mulyandari (Universitas Nusa Putra, 2025)
The potential for major earthquakes in Indonesia requires further analysis of multi-story buildings. This is so that when an earthquake occurs, the building structure is expected to be able to withstand it. One method of analyzing building structures is the pushover method. This method is often used in the analysis of multi-story buildings with less than 10 floors because the rigidity of the structure is still sufficient to support seismic loads. This study will evaluate the performance of steel frame building structures using the pushover method, which will then be converted into seismic fragility curves. The results of the pushover analysis on the building structure along the Y-axis axis can withstand a base shear force of 4400 kN, while along the Y-axis axis, it can withstand 3100 kN. The capacity curve output from the pushover will be converted into a capacity spectrum curve using the formula from ATC-40. The capacity spectrum curve will then be converted into a fragility curve.